Peace Journalism and News Coverage on the Cyprus Conflict. - Ersoy, Metin (Muslim World, 2010)
The article employs the Peace Journalism approach to examine news stories reported in the Turkish Cypriot and Greek Cypriot papers on matters relating to each other and to the Cyprus Conflict. It tests hypotheses about the negative headlines reported in the Cyprus media and the role of Cypriot journalism in peace building and reconciliation between the Turkish and Greek Cypriots. The emergence of Peace Journalism in the 1970s and its evolution during the first Gulf War in the 1990s are also noted.